Attitudes of creativity and development and intention to develop to a business in students of the Agrarian National University - The Molina - Loli, Alejandro (2011)
The objective of the present study is to know the creative and entrepreneurship attitudes, and the intention to start up a business among the students from a Universidad Agraria La Molina. For this purpose, a sample of 262 students was taken. They belong to several majors, enrolled between the first and the last academic term. The results show us that most of the students have a positive attitude towards creativity and entrepreneurship. In the same way, there is a strong relationship with the intention to start up a new business. Furthermore, it was found a positive correlation, when it was conducted an analysis between the entrepreneurship components and the intention of starting a new business. Although, it was not found the same relationship, when it was analyzed the optimism, adaptation capacity, and future vision. Regarding the demographic and social variables and their relationship to the entrepreneurship (low, normal, high) shows a considerable difference, when the working experience and the academic term in which the students are enrolled; are analyzed. In other words, the presence of those variables let us to infer that the different perceptions in the creativity levels and the entrepreneurship. On the other hand, there is not a considerable relationship among the following variables: age, gender, and marital status.